Protective effects of omega-3 essential fatty acids against formaldehyde-induced cerebellar damage in rats - Zararsiz, Ismail; Meydan, Sedat; Sarsilmaz, Mustafa; Songur, Ahmet; Ozen, Oguz Aslan; Sogut, Sadik (Sage Publications Inc, 2011)
This study aimed to investigate changes in the cerebellum of formaldehyde-exposed rats and the effects of omega-3 fatty acids on these changes. The study involved 21 male Wistar-Albino rats which were divided into three groups. The rats in Group I comprised the control group. The rats in Group II were injected with intraperitoneal 10% formaldehyde every other day. The rats in Group III received omega-3 fatty acids daily while exposed to formaldehyde. At the end of the 14-day experimental period, all rats were killed by decapitation and the cerebellum removed. The activities of catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), xanthine oxidase (XO), and malondialdehyde (MDA) levels were determined in cerebellum specimens by using spectrophotometric methods. In our study, levels of SOD and CAT were significantly decreased, and GSH-Px, XO, MDA levels were significantly increased in rats treated with formaldehyde compared with those of the controls. Whereas, it was seen that there was an increase in SOD and CAT enzyme activities and decrease in MDA, XO, and GSH-Px levels in rats administered to omega-3 fatty acids with exposure of formaldehyde. It was determined that exposure of formaldehyde increased free radicals in cerebellum of rats and this increase was prevented by administration of omega-3 fatty acids.
Keywords: Formaldehyde; omega-3 fatty acids; cerebellum; rat